Avaliação de métodos semi-empíricos para estimativa da capacidade de suporte de fundações por estacas pré-moldadas de concreto - Sakata, Luna Miwa Negri (2019)
The present study presents a statistical analysis of static load test results by linear regression and R² coefficient of the bearing capacity of precast pile foundations by semiempirical methods, which reference values was obtained by precast tests static load in the Brazilian technical literature, in piles of different diameters, with their bases assent different depths and installed in various locations in order to ascertain which method has the highest accuracy. The methodology used was reviews in the technical literature, where 20 cases were selected and made statistical analysis of the instrumented prediction. The NSPT geotechnical parameter used was based on the Standart Penetration Test (SPT) in-situ test, after that the performances of the formulations of each method were analyzed, as well as the coefficients used. It was found that the methods of Aoki & Velloso (1975) and Décourt & Quaresma (1978) presented better accuracy for the studied cases, and the methods of Teixeira (1996), Laprovitera & Benegas (1988) and Monteiro (1997) proved to be conservative.